Africa's Debt Crisis: Perspectives on Nigeria's Escape from External Debt Trap - Solomon O. Akinboye (Journal of Global Initiatives, 2010)
In sharp contrast with the image of an "oil-rich" country, Nigeria is paradoxically a heavily indebted poor country. While the country's oil production reached 2.5 million barrels per day in 2004, its total external debt stock at the end of 2004 was estimated at $35.9 billion. The debt crisis has been aggravated by the burden of debt servicing, which has absorbed the nation's budgetary and foreign exchange resources with deleterious impact on the critical sectors of the economy. The paper critically examines Nigeria's external debt profile and efforts toward its alleviation. It argues that the debt burden constitutes a major constraint to the revitalization of the nation's economy, and that its alleviation is imperative for sustainable growth and development.